Oxford new syllabus mathematics 3 - Ban Har, Yeap (Karachi: Oxford University Press., 2024)
Oxford New Syllabus Mathematics 3 is an advanced textbook designed for secondary students, focusing on deepening their understanding of critical mathematical concepts. It covers topics such as algebra, trigonometry, geometry, mensuration, and statistics, emphasizing both theoretical foundations and practical applications. Through detailed explanations, worked examples, and exercises, students are encouraged to apply their mathematical skills to solve complex problems. The book promotes critical thinking and analytical reasoning, preparing students for higher-level mathematics and real-world applications. With a structured and progressive approach, it serves as a key resource for advancing students' mathematical knowledge and competency.